Teachers’ Insights on the Implementation and Significance of Career Guidance in Elementary Schools - Zainab Waheed; Dr. Sidra Kiran; Erum Noreen; Wajid Mahnaz (Indus Journal of Social Sciences, 2025)
This quantitative study aims to investigate Teachers’ Insights on the Implementation and Significance of Career Guidance in Elementary Schools, with the intention of influencing elementary school policy and practice. Career counseling is regarded as a very important element for students. Teachers' perceptions of the need for career counselling services at the elementary school level are examined in this study, with a focus on the link between their opinions and their perceptions. Two primary goals serve as the foundation for this study: 1) to examine the perception of teachers towards the current status of career counseling services at elementary level and 2), to identify the perception of teachers towards the need of career counseling services at elementary level .Quantitative research design used in the present study. 378 elementary public school teachers and 44 public school were overall population of the study at sector Nilore Islamabad. Target population was 180 elementary public school teachers. Sample of the pilot study was 21 elementary public school teachers from 6 public elementary school. Final study of sample was 123 elementary public school teachers from 35 public elementary schools at sector Nilore Islamabad were selected. Simple random sampling technique was used for the selection of sample from public elementary schools. Questionnaire was developed and distributed among teachers in order to collect data. According to 87.0% of respondents, a significant percentage believe that career counselling services are crucial for supporting and improving academic achievement for both boys and girls. The broad belief that career advice is crucial for fostering students' future success is demonstrated by the 84.3% of respondents who agreed. There is broad agreement on the importance of career counselling, as seen by the 83.6% of respondents who agreed. 74.7% shows that there is broad agreement about the need of offering counselling services tailored to a student's gender in order to better meet their unique needs for career development. According to 72.6% of respondents (Agree + Strongly Agree), career counselling programs are essential in reducing elementary school pupils' likelihood of committing crimes. Very few people answered 1.4 percent (2 individuals) strongly disagree. According to 2.1% (3 respondents), there is minimal opposition to the idea that career coaching aids students in overcoming their challenges. The results showed that although teachers acknowledge the value of career counselling in promoting students' growth and directing their future goals, many of them claim a dearth of official programs and inadequate training. Their views of the need for improved counseling services are influenced by this disparity. The study comes to the conclusion that in order to effectively assist students in their career exploration, career counseling has to be improved via focused professional development and resource allocation. To build a supportive atmosphere for professional development in primary school, recommendations include putting in place training programs for teachers, setting up organized counseling services, and encouraging community involvement.